2019
DOI: 10.1149/2.0961908jes
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Windows Based on Reversible Metal Electrodeposition with Enhanced Functionality

Abstract: Electronically tintable windows increase the energy efficiency and comfort of buildings and automobiles. Recently, dynamic windows harnessing reversible metal electrodeposition have been explored as a viable alternative to electrochromic materials. In this manuscript, we first construct 25 cm 2 dynamic windows with two tin-doped indium oxide (ITO) working electrodes, a metal frame counter electrode, and an aqueous-based electrolyte containing metal ions. This arrangement allows metal electrodeposition to occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Therefore, a small amount of HCl is always added to the electrolyte to prevent precipitation. However, the presence of H + can cause hydrogen evolution when the applied voltage is higher than 0.7 V. [25,27] The gathering of bubbles on the surface of the working electrode inhibits metal deposition at the corresponding area.…”
Section: Rmeds For Paper-like Displaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a small amount of HCl is always added to the electrolyte to prevent precipitation. However, the presence of H + can cause hydrogen evolution when the applied voltage is higher than 0.7 V. [25,27] The gathering of bubbles on the surface of the working electrode inhibits metal deposition at the corresponding area.…”
Section: Rmeds For Paper-like Displaysmentioning
confidence: 99%
“…The best performance reported for RMEDs are listed in Table 1.In the last century and the first decade of the 21th century, sustained efforts have been invested to apply the reversible electrodeposition mechanism to display devices. [19][20][21][22][23][24] In recent years, research on RMEDs has been progressing owing to their potential applications in energy-saving fields, especially in light modulation [8,[25][26][27][28] and thermal management. [18,29,30] Ag, Bi, and Cu are the most widely studied metals for reversible electrodeposition because of their high reversibility and the use of hazard-free electrolytes.…”
mentioning
confidence: 99%
“…By comparison, the active components of RME devices can be fabricated using simple solution-based methods. 18,19 Although RME devices have numerous advantages for dynamic window applications, one of the main challenges hindering the development of RME devices is eliciting uniform metal electrodeposition on a large scale with a fast switching speed. In our previous work, we demonstrated that metal electrodeposition uniformity increases by seeding metal growth with a self-assembled monolayer (SAM) of inert Pt nanoparticles on an indium tin oxide (ITO) substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The second exploits reversible electrodeposition by depositing and dissolving metal (Ag, Bi, Cu, Ni, Pb, and others) onto a transparent conducting substrate to modulate its optical properties. [1,2,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] For the electrodeposition-based EC systems, the device structures mainly consist of two opposite transparent electrodes with an electrolyte in-between. The metal dissolved in the electrolyte will be deposited on the electrode surface when voltage is applied to the electrodes.…”
mentioning
confidence: 99%